2020
DOI: 10.14710/parole.v10i2.110-123
|View full text |Cite
|
Sign up to set email alerts
|

Manner Verb Construction and Reduplication of Kedang Language: A Typological Study *

Abstract: This study discusses manner verb construction and reduplication of the Kedang language from the perspective of typology. This study is a descriptive qualitative study by describing the pattern of manner verb construction of the Kedang language. The data is analyzed by using distributional (agih) and identity (padan) methods through breaking down words and sentences. The choice and equivalent of sentences are adjusted with the typology rule of universal language by Dixon (2006); serial verb construction. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Manner serialization is to express the way in which a particular action is performed. In this case, Schapper, (2017) revealed that a person's actions can be transitive or intransitive, while behavioral verbs are always intransitive (Khasanah & Subiyanto, 2020). In addition, Process, movement, and action verbs are the constructing components of the KVS method type.…”
Section: ) Serialization Of Mannermentioning
confidence: 99%
“…Manner serialization is to express the way in which a particular action is performed. In this case, Schapper, (2017) revealed that a person's actions can be transitive or intransitive, while behavioral verbs are always intransitive (Khasanah & Subiyanto, 2020). In addition, Process, movement, and action verbs are the constructing components of the KVS method type.…”
Section: ) Serialization Of Mannermentioning
confidence: 99%
“…Previous studies have extensively investigated the construction of languages, particularly in the realm of direct-motion verb, conducted by various researchers (Subiyanto, 2010;Maghfiroh, 2021;Ummah, 2018;Muttaqin, 2019;Putri & Subiyanto, 2023;Pamphila, 2011;Khasanah & Subiyanto, 2020). Subiyanto (2010) has already examined the construction of motion verb in Javanese language.…”
Section: Literature Reviewmentioning
confidence: 99%